Peningkatan Pelayanan Masyarakat dengan Memanfaatkan OpenSID Sebagai Media Sistem Informasi Digital di Desa Puncaksari - Ardiana, Agus Tri; Amalia Purnama Sari; Hilma Hamimah Maulani (Fisip UIN Sunan Gunung Djati Bandung, 2023)
The Village Government of Puncaksari in the Sindangkerta District of West Bandung has a crucial responsibility to provide efficient and high-quality public services. Currently, the service system relies on manual methods, resulting in various issues such as administrative complexity and the potential loss of vital documents. Therefore, efforts for improvement have been undertaken through the development of a Village Information System (SID) based on a website utilizing OpenSID. The approach used is participatory, involving the empowerment of the community and Village government officials. The results have shown that public services via the website have proven to be effective, saving time, and delivering significant benefits to both the Village government and the local residents.).